A Constitutional Limitation on the Enforcement of Judgments—Due Process and Exemptions - Michael M. Greenfield (Washington University Law Quarterly, 1975)
Since the Supreme Court's decision in Sniadach v. Family Finance Corp., holding the Wisconsin prejudgment garnishment statute unconstitutional, courts and commentators have extensively considered constitutional limitations on creditors' prejudgment remedies. Constitutional limitations on postjudgment remedies, however, have received scant attention even though statutes in every state specify property exempt from execution. The rationale for exempting property is to permit the judgment debtor (and his family) to maintain a minimum standard of living and continue as a productive member of society. To achieve this goal, the substantive provisions of exemption laws are to be liberally construed. But the procedural aspects of exemption laws may actually frustrate their policy. In addition, they may be unconstitutional. This Article will (1) examine whether, under Sniadach and other decisions, the procedural aspects of existing statutes conform to the requirements of due process and (2) propose a postjudgment seizure statute that poses no constitutional objections and fairly accommodates the interests of debtor and creditor.
Keywords: Attachment and garnishment; Due process of law; Execution